Evaluating financial sustainability in the Iraqi economy for the period (1990-2016) - Maitham Khudair Jawad Kazem; Basema Neyaz Muhsen (Iraqi Journal for Administrative Sciences, 2024)
The research aims to address the problem represented by (in light of the growing deficit and increasing public debt: does the Iraqi economy have the ability to achieve financial sustainability), so the research focused on the hypothesis that the Iraqi economy can achieve financial sustainability. To verify this, the research was divided into three sections. In addition, the time limits of the research included the period extending from the years 1990-2016. In conclusion, results were reached, of which the unit root indicates that all the research variables were stable for the first difference. The results also confirmed that public expenditures are growing at a faster rate than revenues. the public. That is, the slope is less than one (0.92), and this indicates Iraq’s inability to repay debts and contain their burdens. Therefore, the research recommends increasing the importance of other revenues by raising the efficiency of border crossings and collecting customs revenues correctly, in addition to building a database of those subject to taxes and holding them accountable if they evade paying them.